Padrão de atividades, comportamento alimentar, exploração de habitat e área de vida de um grupo de Sapajus flavius (Schreber, 1774) (Primates, Cebidae) em um fragmento de floresta atlântica, Paraíba, Brasil - Rodrigues, Keoma Coutinho (2013)
The blonde capuchin monkey, Sapajus flavius , occurs in remnants of Atlantic Forest in Brazil north of the São Francisco River, and is included in the IUCN red list as "Critically Endangered". Studies of the behavior and eating habits, exploitation and habitat the pattern of use of space are important, since there is a gap of information to species. Such information will assess how populations of S. flavius are living in forest fragments, enabling the deployment of more effective conservation actions. The study objectives were to describe the activity budgets, feeding behavior, the size of the home range and habitat exploitation pattern of a group of blonde capuchin monkey in RPPN Engenho Gargaú located in the municipality of Santa Rita (Paraíba). Data were collected by scan sampling method with instant records every 5 minutes. Phenological data were collected monthly from 90 vegetables fruiting specimens whose intensity were calculated using the Activity Index. The Scan Sampling was dominated by the travel (38.96%), followed by feed (28.58%), forage (21.66%), rest (4.77%), agonistic behavior, social, vocalization and drinking water (6%). This pattern varied significantly during the dry and rainy season. The food was more frequent in the dry season and the displacement in rainy season. The diet group was composed of fruit (43%), stalks of sugar cane (30%), prey animals (15%), leaves (7%), plant parts, including sheath, petiole, bark (3%) and flowers (2%). In the rainy season, fruit consumption was significantly higher and was positively correlated with the intensity of fruiting. The consumption of sugar cane was higher in the dry season, when fruit production was low. 48 plant species were identified in the diet, being Saccharam sp. (37.83%), Elaeis spp. (16.99%) and Tapirira guianenses (6.22%) the most important. The home-range calculated by the Minimum Convex Polygon (MPC) for the group was of 240.22 hectares. The habitats more explored were in Regeneration Forest (35.5%), Edge of Forest in Regeneration (28.2%), Edge of Flooded Mature Forest (17.5%), Edge of mature forest (9.6%) and mature forest (9.2%). The pattern of activities, diet and living area were consistent to those found for the genus Sapajus and all aspects were influenced by the seasonality of food resources and the intervening matrix composed predominantly of sugar cane.